Anatomy of Ghana's parliamentary elections and democratic consolidation. Issue 3 (2nd July 2020) - Agomor, Kingsley S.; Adams, Samuel; Asante, William
ABSTRACT: Determinants of electoral patterns and voter decisions in Ghanaian politics and in the politics of many other African countries have engaged the attention of many scholars. This paper, however, departs from conventional study of voter behaviour to specifically focus on swing voters and what informs their voting decisions on Parliamentary candidates. The study obtained primary data from a nationwide survey of 3, 160 voters who have voted more than once over the period 1992–2016 but also voted in 2016. The descriptive and logistic regression results show that the ability to develop one's locality, campaign message and human relation of the candidate were the key factors that influenced voters' choices. The study demonstrates that the Ghanaian voter has defied what has been described as 'ethnic census' about African voting behaviour. Promoting the public good and having a good relationship with people were key factors that influenced the vote choice.